Government Expenditure in Agriculture Sectors and its Impact on Economic Growth - Bhattarai, Shom (NPRC Journal of Multidisciplinary Research, 2025)
This paper aims to access the level of government expenditure in agriculture sectors and its impact on economic growth in Nepal. This research follows the quantitative methods based on secondary data specifying on economic survey report, eighteen fiscal years 2005/06 to 2023/24. The data reflects significant trends in the contributions of agriculture and non-agriculture sectors to the Gross Domestic Product (GDP). This paper mainly emphasizes on the Nepalese agriculture sector which traditionally shows a crucial role in the economic growth however, it is found not to be steady growth but it is reflecting the gradual decline in the economic activity and development. In 2005/06, share of agriculture in GDP was 32.37 percent, the ratio of economic growth is found to be decreased by 21.18 percent in 2023/24. As economies growth level shows the contribution of agriculture to GDP typically reduces due to factors of mechanization, rural-urban migration, and the growth of other sectors by manufacturing, services, and technology. Thus, the agriculture sector's GDP contribution is clearly trending downward, while the non-agriculture sector's importance is continuously rising. Therefore, this paper could be significant on reflecting the recent economic trends to evaluate government expenditure ratio in the sector for transformation of agricultural development in Nepal, and it would be also helpful to address the challenges for policymakers in the path of sustainable growth along with spirit of inclusive development.